Midazolam daytime residual effect evaluated by the multiple sleep latency test - Rubens Reimão (Arquivos de Neuro-Psiquiatria)
Daytime sleepiness after ingestion of midazolam as a hypnotic was quantitatively studied employing the Multiple Sleep Latency Test (MSLT). We evaluated 20 healthy volunteers, 10 of which received a single oral dose of midazolam (15 mg, one tablet) and 10 of which received placebo, in a double-blind design. Tablets were administered at 2200 h, bedtime. On the following day, all subjects were submitted to a clinical evaluation, a subjective checklist and the MSLT. The mean age was 34.7 + 8.9 years in the midazolam and 38.0+10.6 years in the placebo groups (n.s.). Sex and weight distributions were similar in both groups (n.s.). Clinical evaluation and subjective symptom checklist did not make evident significant differences between midazolam and placebo groups (n.s.). The MSTL was performed at 0900, 1100, 1300, 1500 and 1700 h. Mean sleep latencies were 12.0, 12.7, 8.0, 13.5, 17.0 min in the midazolam group; mean sleep latencies were 13.8, 9.0, 6.9, 9.5, 13.6 min in the placebo group (n.s.). In the single dose, double-blind design here evaluated, midazolam did not show differences in relation to placebo on the following day, detectable by the MSLT.